Multiple Intelligence Type Profile of Prospective Physics Teacher Students: Recommendations for Lecture Methods to Create a Superior and Globally Competitive Generation - Hikmawati Hikmawati; Muhammad Taufik; Jannatin Ardhuha; Satutik Rahayu; Irman Muliadi (Universitas Hamzanwadi, 2024)
The type of multiple intelligence possessed by students can be a consideration for lecturers in determining the right lecture method so that it can create effective learning. The effectiveness of learning has an impact on the quality of superior and competitive student competencies. This study aims to analyze the distribution of multiple intelligences of students and relate them to relevant learning methods in the Physics Curriculum Review course in the Physics Education Study Program, University of Mataram. The subjects of the study were 22 class 5C students who took the multiple intelligence test. This study uses a descriptive approach with quantitative data analysis. The study was conducted in August 2024. The instrument used to view the profile of students' multiple intelligence types can be accessed through the online platform